Development of a UAV based framework for CH4 monitoring in sludge treatment centres - Hiniduma Gamage, Kavindi; Bajón Fernández, Yadira; Srinamasivayam, Bharanitharan; Turner, Duncan; Rivas Casado, Monica (MDPI, 2023)
With the increasing trend in the global average temperature, the UK’s water industry has committed to achieve Net Zero by 2030 and part of this includes cutting CH4 emissions from sludge treatment facilities. Currently, emissions are estimated following the carbon accounting workbook guidelines and using default emission factors. However, this method might not be a true representation of emissions as these vary depending on many factors. The use of unmanned aerial vehicles (UAVs) has proved cost effective for environmental monitoring tasks requiring high spatial resolution information. Within the context of CH4 emissions and in the last decade, the technology has been curtailed by sensor weight and size. Recent advances in sensor technology have enabled the development of a fit-for purpose UAV CH4 sensor (U10) which uses Tuneable Diode Laser Absorption Spectroscopy. This study intends to develop a framework for CH4 data collection strategies from sludge treatment centres using UAV-U10 technology and asset level CH4 enhancement estimations based on geostatistical interpolation techniques and the mass balance approach. The framework presented here enables the characterization of spatial and temporal variations in CH4 concentrations. It promotes asset level CH4 enhancement estimation based on on-site measurements.
Keywords: sludge treatment centre; UAV; open-path TDLAS; enhancement estimation